Partisipasi Perempuan Pada Program Akademi Paradigta Dalam Pelaksanaan Pendidikan Kepemimpinan Perempuan Di Kecamatan Ringinarum Kabupaten Kendal - Wulandari, Meti Ayu; Siti Andarwati; Dina Ruslanjari (Pusat Studi Wanita dan Keluarga UGM, 2025)
This study aims to analyze women's participation in the Paradigta Academy Program, particularly in the implementation of women's leadership education at the village level. The Paradigta Academy is a community empowerment program designed to strengthen the role of women in village leadership through training, group discussions, and field practice. This study identified various forms of participation by women participants, such as thought participation (submission of ideas), labor participation (contribution of time and physical labor), skill participation (contribution of skills in practical activities) and money participation. The research method used is descriptive qualitative with data collection through observation, documentation and interviews. The results showed that women's involvement not only improved the knowledge and skills of individual participants, but also strengthened social networks and community capacity in dealing with village issues. The program effectively created space for women to play an active role in the decision-making process and promoted an inclusive and collaborative leadership model. Women's participation in the program also showed a positive impact in raising social awareness and encouraging women's role as agents of change in the village environment. It is recommended that this program continue to be developed and supported by the local government.